Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPA pada Materi Siklus Hidup Hewan Menggunakan Game Edukasi Media Puzzle - Nurasia, Nurasia; Indah, Opik Dwi; Ismayanti, Ismayanti; Misbah, A.M. Nur Musaysar (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2023)
The aim of this research is to improve the learning outcomes of fourth grade students through educational games with puzzle media in science subjects at SDN 2 Pinceppute. The type of research used is Classroom Action Research (PTK) which was carried out for 2 cycles. The subjects studied were 16 grade IV students at SDN 2 Pinceppute, consisting of 9 male students and 7 female students. Data collection was carried out using a student learning achievement test instrument. Data analysis used is descriptive data analysis. The results of the study show that educational games through puzzle media can improve the learning outcomes of fourth grade students at SDN 2 Pinceppute, Palopo City. This can be seen from the indicators of research success, where ≥ 75% of students have achieved the KKM score (70). In cycle I, the number of students who had completed were 8 students (50%) and those who had not completed were 8 students (50%). Cycle II increased to 13 students (81.25%) and 3 students (18.75%) did not complete. It can be concluded that student learning outcomes have increased by 31.25%. Keywords: student learning outcomes, educational games, media puzzle,               science learning .